Decompression Sickness: A Rarely Encountered Case in Forensic Medicine Practice - Meral, Orhan; Kaya, Ahsen; Aktaş, Ekin Özgür (The Bulletin of Legal Medicine, 2018)
Decompression Disease, also known as Caisson Disease, is a condition caused by bubbles formed by inert gases (Nitrogen, Helium, etc.) dissolved in blood and tissues under pressure and is usually seen in divers. These inert gases, which are dissolved by the action of decreasing pressure, come out of solution and form bubbles in vessels and tissues resulting in prevention of tissue nutrition. This condition may produce no symptoms; however, it also may result in a wide range of pathologies from simple fatigue to dyspnea, paraplegia and even death. A 41-year-old male patient who applied to the Forensic Medical Polyclinic with a request for report and developed a “Decompression Disease” resulting from rapid water surface elevation from 27 meters in depth at sea according to the received story is presented as a rare case in forensic medicine practice and to emphasize the forensic medical approach in such cases.
Keywords: decompression disease; alterations of pressure; forensic medicine